Is he the culprit? - Prabhan, BB; Shrestha, S (Nepalese Heart Journal, 2013)
The peripartum cardiomyopathy (PPCM) generally occurs in the last trimester of pregnancy or within 6 months of delivery. The disease generally occurs in multiparous female more than 30 years of age. The prognosis depends upon whether the heart returns to normal size after the first episode of CHF. If heart remains enlarged or the ejection fraction remains depressed after 6 months, the prognosis is poor. We present a case of 27 years female who gave birth to her fourth child and presented peripartum cardiomyopathy 11 months after the child birth. She was admitted, evaluated and managed with diuretics in the initial period and when stabilized placed on ACE inhibitor and alpha beta blocker. She improved significantly and was discharged. She was on regular follow up and showed a significant improvement in heart size, ejection fraction and valvular function when re-evaluated after 7 months. DOI: http://dx.doi.org/10.3126/njh.v8i1.8336 Nepalese Heart Journal Vol.8(1) 2011 pp.37-39